Binary Memory Implemented by Using Variable Gain Amplifiers With Multipliers - Petržela, Jiří; Šotner, Roman (IEEE, 2020)
This work describes design process toward fully analogue binary memory where two coupled piecewise-linear (PWL) resistors are implemented using novel network topology with voltage gain amplifiers (VGA). These versatile active devices allow slopes of individual segments of ampere-voltage (AV) characteristics associated with PWL two-terminals to be electronically adjustable via external DC voltage. Numerical analysis of designed memory cell covers all mandatory parts: phase portraits, calculation of the largest Lyapunov exponent (LLE), basins of attraction for the typical strange attractors, and high resolution circuit-oriented bifurcation sequences. A transition from the stable states toward chaotic regime through metastability is proved via real measurement. The robustness of the generated chaotic attractors is verified by captured oscilloscope screenshots.

This work describes design process toward fully analogue binary memory where two coupled piecewise-linear (PWL) resistors are implemented using novel network topology with voltage gain amplifiers (VGA). These versatile active devices allow slopes of individual segments of ampere-voltage (AV) characteristics associated with PWL two-terminals to be electronically adjustable via external DC voltage. Numerical analysis of designed memory cell covers all mandatory parts: phase portraits, calculation of the largest Lyapunov exponent (LLE), basins of attraction for the typical strange attractors, and high resolution circuit-oriented bifurcation sequences. A transition from the stable states toward chaotic regime through metastability is proved via real measurement. The robustness of the generated chaotic attractors is verified by captured oscilloscope screenshots.
Binary Memory Implemented by Using Variable Gain Amplifiers With Multipliers
Keywords: Analogue binary memory; bifurcation diagram; electronic tuning; chaos; Lyapunov exponent; piecewise-linear (PWL) resistors; strange attractor; Analogue binary memory; bifurcation diagram; electronic tuning; chaos; Lyapunov exponent; piecewise-linear (PWL) resistors; strange attractor